Cost‐effective energy harvesting at ultra‐high concentration with duplicated concentrated photovoltaic solar cells. Issue 8 (7th April 2020) - El‐Gahouchi, Mohamed; Aziziyan, Mohammad Reza; Arès, Richard; Fafard, Simon; Boucherif, Abderraouf
Abstract: Concentrated photovoltaic (CPV) systems are one of the few technologies that can provide cost reduction while offering efficiency improvement. In this respect, the resistive losses are some of the main limiting factors, which restrict the efficiency improvement and the cost reduction at ultrahigh concentrations (UHCs). In this work, we propose and investigate new designs consisting of duplicated junction solar cells. The approach can resolve the issues related to the resistive losses. Simulation results, based on Shockley‐Queisser limit, demonstrate that the detrimental effects of series resistance losses in the degradation of efficiency at UHC factor can be mitigated with this strategy. The modeled structures are composed of multiple junctions of materials (GaInP, GaAs, and Ge), which are lattice‐matched to Ge or GaAs. These results illustrate the potential of duplicated junction designs for enhancing efficiency of III‐V solar cells under high concentrations, exceeding 1000 suns (under AM1.5D solar spectrum at 300 K). Finally, a relative cost calculation indicates that more than 30% of cost reduction can be achieved using these designs at UHCs. Abstract : Duplicated junction solar cell, as an innovative design of structure for enhancing efficiency at ultrahigh concentrations, is proposed and investigated. Based on a semi‐empirical model, an efficiency over 46% at 8000 suns is demonstrated for three times duplicated GaInP/GaAs/Ge solar cells. A detailed cost analysis revealed 30% reduction of expenses for the 3‐time duplicated GaInP/GaAs/Ge solar cells, for concentration factors over 5000 suns.